Metaphors for Malaysia’s Economic Transformation Programme - Kumaran Rajandran (Kajian Malaysia, 2013)
This article explores the Malaysian Prime Minister's choice of metaphors to conceptualise Malaysia's Economic Transformation Programme (ETP) by studying a sample of the Prime Minister's texts about the ETP. These texts include the Prime Minister's Foreword in the ETP Report and his periodic Progress Updates released between 2010 and 2011. A qualitative close reading, using critical metaphor analysis, reveals that the role of metaphor in these texts is to implicitly evaluate the ETP positively. The two major conceptual metaphors identified here are ETP IS A JOURNEY and ETP IS A VEHICLE. Such conceptual metaphors naturalise a binary and dependent relationship between the government as expert and citizens as non-experts in economic matters. Such rhetoric thus helps to justify the tradition of government intervention in the economy. The other conceptual metaphors identified are ETP IS A PLANT and UP IS GOOD, both of which posit that increasing economic and social advantages result from the ETP. All these conceptual metaphors enhance the government's claim to economic experience and leadership by legitimising the ETP as an effective policy in transforming Malaysia into a developed country. These conceptual metaphors might be part of a larger strategy to portray the government positively among citizens, as having sustainable economic development policies could provide a crucial electoral advantage to the government in the upcoming general elections.